Examining Undergraduate Students’ Conceptions of Inquiry in Terms of Epistemic Belief Differences - Getahun, Dawit Asrat; Saroyan, Alenoush; Aulls, Mark (Canadian Journal of Higher Education, 2016)
The purpose of the study was to examine undergraduate students’ conceptions of inquiry and the relationship of inquiry conceptions to epistemic beliefs. Data were obtained from 107 university students (80 female, 27 male) using an open-ended questionnaire to examine their conceptions of inquiry and Schommer’s Epistemological Beliefs Questionnaire to group participants as naïve or sophisticated in their epistemic beliefs. Data analyses revealed that participants with sophisticated epistemic beliefs had multidimensional conceptions of inquiry and provided conceptually rich definitions. Students with naïve beliefs, on the other hand, revealed more simplistic and indistinct conceptions of inquiry and either described it with few details or stated that they did not know about it. The study in general indicated the presence of a relationship between epistemic beliefs and inquiry conceptions, implying that any practical effort to change the way students conceptualize a phenomenon in general and inquiry in particular needs to take into account their epistemic beliefs.